Artificial intelligence in the service of voice and speech forensics - Šešum, Mia; Šestić, Marina; Ivanović, Maja (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Artificial intelligence represents the pinnacle of modern technological development. Designed to assist humans in performing tasks that are burdensome or even exceed human capabilities, this computer-based system finds application in various areas of professional and everyday functioning. One of the fields where the resources provided by artificial intelligence can be of particular value is forensic science. Objective. The aim of this paper is to present, through a review of the available literature, the potential applications of artificial intelligence in the context of voice and speech forensics, its limitations, and the potential risks associated with its use in judicial proceedings. Methods. The literature used in this study was obtained by searching accessible databases via remote access, followed by a synthesis of relevant findings. Results. Artificial intelligence is a highly sophisticated technological advancement with the potential to transform various forensic disciplines in the future. Due to the fact that language is one of the most complex social phenomena, as well as the consequences that could arise from analyses whose inner workings are not transparent to expert witnesses, this technology has not yet been included among the officially recognized and accepted methods of voice forensic analysis. Conclusion. Artificial intelligence can contribute to forensic voice and speech examinations. However, given that the lack of transparency of such systems raises fundamental ethical concerns, its application remains, for the time being, limited to operations conducted during the preparatory phase of forensic analysis. Increasing the transparency of AI-based systems, along with ongoing efforts to improve their robustness and accuracy, will help resolve ethical dilemmas and support the acceptance of this technology as legitimate within judicial proceedings.
Keywords: voice and speech; Automatic identification; biometry; forensic; artificial intelligence